2017
DOI: 10.1016/j.ijsu.2017.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Decompression and coflex interlaminar stabilisation compared with conventional surgical procedures for lumbar spinal stenosis: A systematic review and meta-analysis

Abstract: Compared with conventional decompression plus fusion surgery, coflex was not inferior in terms of functional clinical outcomes, including ODI and VAS pain score. Moreover, coflex showed less blood loss, shorter LOS and similar device-related complications compared to decompression plus fusion surgery. Therefore, the coflex interlaminar stabilisation device was found to be safe and effective compared to decompression plus fusion for the treatment of LSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…Similar to our findings, Li et al concluded that D+F showed less favorable outcomes in terms of ODI, length of hospital stay, and blood loss in comparison with D alone (using coflex). They did not find any significant difference in VAS and major device-related complications, which is in contrast to our findings [ 24 ]. Another international study showed that both the D and D+F groups resulted in reduced VAS LP and BP [ 25 ].…”
Section: Reviewcontrasting
confidence: 99%
“…Similar to our findings, Li et al concluded that D+F showed less favorable outcomes in terms of ODI, length of hospital stay, and blood loss in comparison with D alone (using coflex). They did not find any significant difference in VAS and major device-related complications, which is in contrast to our findings [ 24 ]. Another international study showed that both the D and D+F groups resulted in reduced VAS LP and BP [ 25 ].…”
Section: Reviewcontrasting
confidence: 99%
“…A recent study by Bae et al also compared decompression and ILS to decompression and instrumented spinal fusion; CCS rates for patients treated with ILS were shown to be statistically superior, demonstrating the benefits of ILS in terms of durability [8]. However, regarding complications associated with ILS, similar rates were seen in both decompression with fusion and decompression with ILS [15]. Randomized prospective trials with a longer follow-up duration are needed to evaluate outcomes and device-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…The distraction force also enlarged the intervertebral foramen and reduced the load on the intervertebral disc and the facet joint in flexion. The meta-analysis by Ai-min Li [27] showed that Coflex was more effective than PLIF in terms of decompression, the Oswestry Disability Index (ODI), length of hospital stay (LOS) and blood loss. Wei yuan [28] held that Coflex surgery had significantly less blood loss, shorter hospital stay and operative time than PLIF (p < 0.001), and it also had a lower reoperation rate for ASD than PLIF, yet with no statistical difference (11.1% vs. 4.8%, p = 0.277).…”
Section: Discussionmentioning
confidence: 99%